Semiotic Analysis of the Little Mermaid Movie Poster Using Peirce (1996) - Wicaksono, Lanang Dwi; Heriyati, Nungki (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
Movie poster has a commercial value and is used to advertise the movie. This research is conducted to analyze the sign depicted as well as the meaning from the Little Mermaid movie poster. This research used qualitative descriptive analysis method to explain the sign and its meaning. Furthermore, Semiotic from Charles Sander Peirce is used to analyze the sign and its meaning. To support the analysis, various journals and books are used as the reference. The result of this study indicated that there are two types of signs found in movie posters, namely qualisign and sinsign. The Little Mermaid movie poster also contained two different kinds of objects, namely Icons and Indexes, where the index is also further divided into spatial and temporal indexes. The last thing from the poster found was the interpretant which is the connection and the meaning of signs and objects. From the result, it can be concluded that each sign that depicted in the movie poster is represented well, not only through the visual one, but also the non-verbal one. It is because we could also get an official information on where we can find or see the movie, which is very crucial for the movie poster. Keywords: Semiotics, Peirce, Sign, Object, Interpretant